The Effect of Sulfur (S) – Silicate (Si) Fertilizer Application on The Growth, Yield, and Physiochemical Properties of Two Soybean Varieties - Slameto Slameto (Universitas Sebelas Maret, 2023)
Soybeans are a food ingredient with a high level of consumption in Indonesia. Low soybean production needs to be increased in productivity and quality by managing soil fertility through fertilization. This research aims to determine the effect of applying Sulfur-Silicate fertilizer to two soybean cultivars, Devon and Dena, and their interaction on soybean productivity and quality. The method used in this research was a randomized block design with 2 treatment factors, namely soybean variety and Si-S fertilizer concentration. The level of treatment for the soybean varieties used are the Devon and Dena1 varieties. The Si-S fertilizer concentration levels tested were without fertilizer, Si-S 110mg/L-23 mg/L; 133 mg/L-30.7 mg/L; 200 mg/L-46 mg/L. Data were analyzed statistically and processed using Duncan's multiple range test. Treatment of Si-S 200 mg/L - 46 mg/L on Devon soybeans increased the average Plant Height to 91.00 cm, Plant Diameter to 0.90 cm, Number of Leaves to 72.0, Number of Branches to 5.33, and the chlorophyll content becomes 35.50, while Dena1 soybeans were 85.0 cm, 0.90 cm, 80.6 cm, 5.6 and 36.50 respectively. Treatment using 110mg/L-23 mg/L Si-S fertilizer increased seed weight, number of pods per plant and weight of 100 seeds. The results of the research show that applying Si-S fertilizer to Dena1 variety soybean plants can increase productivity in terms of the number of pods and seed weight. It is hoped that these results will provide education to farmers regarding the application of Si-S fertilizer and soybean varieties to increase soybean yield and quality.